The Emotion-Aware City - Oliveira, Tiago H. Moreira de (2021)
De Oliveira, T. H. M. (2015). The Emotion-Aware City: Using Ambient Geographic Information (AGI) in order to understand emotion & stress within smart cities. In 3rd AGILE PhD School Association of Geographic Information Laboratories for Europe, AGILE PhD School 2015 (Vol. 1598, pp. 1-5). (CEUR Workshop Proceedings).